Imag(in)ing the Buddhist Brain: Editorial Introduction - Colzato, Lorenza S. (Zygon, 2010)
Abstract. Buddhism has captured the imagination of many in the modern (Western) world. Recently, scientists have seemed eager to discover whether claims about Buddhist meditation can be verified experimentally. Brain research is beginning to produce concrete evidence that mental discipline and meditative practice can change the workings of the brain and allow practitioners to achieve different levels of awareness, as measurable for instance in reaction times to stimuli. The goal of this section of articles in Zygon is to address recent developments in this area. The contributions address a wide array of questions, although they certainly do not cover the whole ground of what one may consider “problems” of meditation. Yet, we believe that the issues addressed here have widespread implications and that they constitute a strong argument for the richness of the meditation domain.